2020
DOI: 10.37939/jrmc/vol24.iss1.11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bacterial Vaginosis in Females of Child-Bearing Age and Utility of pH and Whiff Test in Diagnosis

Abstract: Background: To determine the prevalence of bacterial vaginosis among females of reproductive age and assessment of the effectiveness of pH and the Whiff test in its diagnosis. Methods: This was a cross-sectional study. A total of 100 subjects were included, coming with a complaint of vaginal discharge. The bacterial vaginosis was diagnosed by using the Nugent scoring system, Whiff and pH tests. The prevalence was calculated by descriptive statistics and using the Chi-square test and results were shown in perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Firstly, it was observed that the pH level increases in patients with bacterial vaginosis [ 35 , 36 ] and patients showing abnormal vaginal discharges [ 37 ]. One question was whether vaginal pH measurements, which are associated with the presence of abnormal vaginal discharges, could be used as a simple diagnostic strategy for bacterial vaginosis.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it was observed that the pH level increases in patients with bacterial vaginosis [ 35 , 36 ] and patients showing abnormal vaginal discharges [ 37 ]. One question was whether vaginal pH measurements, which are associated with the presence of abnormal vaginal discharges, could be used as a simple diagnostic strategy for bacterial vaginosis.…”
Section: Discussionmentioning
confidence: 99%